Insights from EFL Classroom: Strategies for Teaching English from Experienced Teacher - Cahyani, Adisthy; Rahim, Titin Rahmiatin; Aradhanawaty, Syenja (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study explores effective strategies for teaching English as a Foreign Language (EFL) by drawing on insights from experienced teacher. Through qualitative interviews and classroom observations, the research identifies key strategies that have been implemented by the teacher in EFL classroom. The participant of this study was an experienced teacher who have been working as an English teacher for 36 years. The participant was chosen purposively as most of students considered him as a good teacher. The findings highlight that during the teaching process, the teacher incorporate controlled technique such as warming up, setting, organizational, content explanation, reading aloud, checking, question-answer, drill, translation, dictation, copying, and review. Additionally, the teacher also applied semi-controlled technique such as brainstorming, question-answer and preparation then for free technique such as problem solving, interview and discussion in responding to diverse student needs. These insights provide valuable guidance for EFL educators seeking to improve their instructional practices and foster better language outcomes for their students.